Editorial - Teye, Prof. G. A. (UDS International Journal of Development, 2022)
The UDS International Journal of Development (UDSIJD) has published the second Issue for 2021 (Volume 8, Issue 2). This Issue has a total of eight articles; two in the Health Sciences, two in the Agricultural Sciences, and four in the Humanities. The Journal continues to be an academic hub aimed at contributing to development by providing open access research that cut across a wide range of developmental issues. We entreat researchers, academics, and authors from varied fields to submit novel research manuscripts for consideration and publication since the Journal provides a platform to share findings and knowledge beneficial to readers in Ghana, Africa and across the globe. The Editorial Team wishes to sincerely thank the University Management, authors, reviewers and staff of the Journal and all those who in diverse ways have supported in making this issue of the Journal a reality. The Editor-in-Chief Prof. G. A. Teye